Freedom and the Iranian Women's Movement. (August 2019) - Mahmoudi, Hoda
The women of Iran are intimately familiar with repression and segregation. Iran's mandatory dress code—veiling—is but one of many restrictions that regulate and control women's bodies and shape their sense of agency and freedom.